IMPLEMENTASI KEBIJAKAN SERTIFIKASI HALAL PRODUK USAHA MASYARAKAT DESA JAYANTI BERBASIS KOMUNIKASI - Intania, Erlin; Rahayu, Sri; Putri , Tania; Arma, Nur Ambia (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
The aim of this research is to analyze the implementation of government policy in empowering the community to have their own awareness to register their halal products through halal assistance officers under the auspices of the Ministry of Religion. The research method used is a qualitative descriptive research method because researchers carry out direct observations in the field, to see directly what actually happens in the field. The analysis technique used is the interactive model Miles, Huberman and Saldana (2014:14). From the research conducted, it was found that the implementation of policies related to Halal Certification in Jayanti Village was not optimal because one aspect was the main factor why the implementation of the policy had not been fulfilled. This indicator is a lack of coordination and communication so that the implementation of this policy has not run optimally